Skype Supervised, Individualized, Home-Based Rehabilitation Programs for Individuals With Rett Syndrome and Their Families – Parental Satisfaction and Point of View - Lotan, Meir; Ippolito, Elena; Favetta, Martina; Romano, Alberto (Frontiers in Psychology, 2021)
Individuals with Rett syndrome (RTT) experience impaired gross motor skills limiting their capacity. Therefore, they need support to participate in physical activities, and it is crucial to work with primary caregivers when developing appropriate strategies, thereby leading to an active lifestyle. There is limited evidence supporting the effectiveness of remotely supported physical activity interventions. This project aimed to evaluate the effects of a skype based, telehealth-delivered physical activity program carried out by participants' parents at home. This article will focus on parental points of view. A mixed-methods design evaluating parental satisfaction was conducted. Forty participants with a confirmed genetic diagnosis of RTT and their families were recruited. The intervention included a 12-weeks individualized daily physical activity program carried out by participants' parents and bi-weekly supervised by expert therapists. Parents' impressions and feelings related to the program implementation were collected throughout semi-structured interviews, and an ad hoc developed questionnaire and discussed. The current project results suggest that a remote physical rehabilitation program, supported fortnightly by video calls, represents an effective way of conducting a remote physical therapy intervention for this population and that it can be easily carried out at home by primary caregivers, promoting positive functional changes, without bringing feelings of frustration due to the required workload. The strategies that families have learned during the program to support the motor activities of their daughters represent an easily performed set of tools that they can maintain and use in everyday life even after the cessation of the program.